Globalisation and development - Sen, Sunanda (New Delhi National Book Trust, India, 2007)
Articles chiefly with reference to India.
Includes bibliographical references (pages [117]-119).
Keywords: Globalization -- Economic aspects -- India; Economic development -- India; India -- Economic policy -- 1991-.